2001
DOI: 10.1001/archotol.127.10.1265
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine With or Without Clonidine Improves Pediatric Tonsillectomy Pain

Abstract: Preincisional injection of ropivacaine with clonidine prior to tonsillectomy has a preemptive analgesic effect that outlasts the local anesthetic and decreases pain, opioid use, and the time to return to normal activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 17 publications
3
80
0
1
Order By: Relevance
“…a more local effect at the level of the injured perianal nerves. Both Gianonni et al 17 and Lavand'homme and Eisenach 18 have described the potent effects of peripheral administration of a mixture of local anesthetics and clonidine when injected close to injured nerves or nerve endings. Opioid medications added to local anesthetic solutions have also been shown capable of prolonging the duration of peripheral nerve blocks.…”
Section: Discussionmentioning
confidence: 99%
“…a more local effect at the level of the injured perianal nerves. Both Gianonni et al 17 and Lavand'homme and Eisenach 18 have described the potent effects of peripheral administration of a mixture of local anesthetics and clonidine when injected close to injured nerves or nerve endings. Opioid medications added to local anesthetic solutions have also been shown capable of prolonging the duration of peripheral nerve blocks.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Various preclinical and clinical studies have reported that clonidine produces antinociception regardless of the route of administration (central or peripheral). [16][17][18][19] Topical administration of clonidine elicits antinociception by blocking the emerging pain signals at peripheral terminals through alpha 2 adrenoceptors without producing the undesirable central side effect observed after systemic administration. 20 In a dose response study, it was demonstrated that iv clonidine 3µg/kg was more effective than clonidine 2µg/kg for postoperative pain relief after hemilaminectomy, while clonidine 5µg/kg resulted in same analgesia with significant side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Binding of α 2 agonists to adrenoceptors in the spinal cord produces analgesia (5). There are several studies that have reported about the use of clonidine, an α 2 agonist, for postoperative analgesia as an infiltration agent (6)(7)(8). Dexmedetomidine has eight times stronger α 2 agonist effects than clonidine and there are studies asserting that the intravenous, intramuscular, intrathecal, epidural, and perineural use of this agent enhances the anesthetic and analgesic effects.…”
Section: Introductionmentioning
confidence: 99%